Targeted delivery of anti-inflammatory cytokine by nanocarrier reduces atherosclerosis in Apo E−/- mice. (January 2020) - Kim, Manse; Sahu, Abhishek; Hwang, Youngmin; Kim, Gi Beom; Nam, Gi Hoon; Kim, In-San; Chan Kwon, Ick; Tae, Giyoong
Abstract: Unresolved inflammation is a hallmark of many deadly diseases including atherosclerosis, a silent pathological condition behind majority of cardiovascular diseases. Yet, anti-inflammatory drugs are not clinically used in the treatment of patients with atherosclerosis. The currently approved treatment regimen against atherosclerosis is mainly focused on lowering the cholesterol/lipid levels in blood and has little to do with controlling inflammation, the underlying cause. Recent preclinical and clinical data suggest that effective alleviation of inflammation in the atherosclerosis plaque could reduce the risk of cardiovascular disease. In this work, we have encapsulated interleukin-10 (IL10), a multipotent anti-inflammatory cytokine into cRGD conjugated pluronic based nano-carriers (NC) for targeted delivery to atherosclerotic plaques. The NC could encapsulate the therapeutic protein with a high loading efficiency in a mild condition and showed sustained release capabilities. The efficacy of cytokine encapsulated NC was analyzed in vitro using the lipopolysaccharide stimulated macrophage cells and in vivo using an established apolipoprotein E-knockout (ApoE −/- ) C57BL/6 mouse model. Compared to free IL10, intravenous administration of NC encapsulated IL10 resulted in vastly improved pharmacokinetic profile and profoundly high accumulation of the cytokine in the atherosclerosis lesions. IL10 delivered by NC was bioactive and reduced the production of pro-inflammatory cytokine IL-1β in the lesion and led to significant regression in the plaque size. These results signify the prospect of nanoparticle based cytokine delivery for preventing atherosclerotic through inflammation modulation in near future.